If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-3.5f=14
We move all terms to the left:
5-3.5f-(14)=0
We add all the numbers together, and all the variables
-3.5f-9=0
We move all terms containing f to the left, all other terms to the right
-3.5f=9
f=9/-3.5
f=-2+2/3.5
| k−10–1=0 | | 1/3(x+6)=2/3x+5 | | h-106=351 | | 5+3.5f=14 | | 55-0.25c=45-0.35c | | 99h+25=89h+45 | | 3(20/19)+5y=15 | | +5+6v=1+5v+3 | | 14)x/4=-3 | | 3x+5(20/19)=15 | | 2n+8=18n+3 | | 19,821.20=60m+2,000 | | 3p+2p=30 | | 1-3n=20.5 | | 3/2n=45 | | 60m+2,000=19,821.20 | | 80=4+4v | | 6(a)+9=75 | | 129=10+7a | | 5+3(x+7)=50 | | -88-10x=-17x+3 | | 3k-2(3k-3)=46+2k | | 3/m+-3=-8 | | 45x=20(x+2) | | 13=6+7n | | 49v^2=-10-49 | | 45x=20x+2 | | 18+9(f)=75 | | 45x=209x+2 | | 48v^2=-10-49 | | 18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−2 | | 18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7)18x+14−24x=−2(3x+7) |